The Limits of Liberty : Mobility and the Making of the Eastern U.S.-Mexico Border - Nichols, James David (Borderlands and transcultural studies., 2018)
"The Limits of Liberty chronicles the formation of the U.S.-Mexico border from a unique vantage of how "mobile peoples" assisted in constructing the international boundary from both sides"--